INTEGRATED APPROACH IN THE MANAGEMENT OF BRONCHIAL ASTHMA: A RETROSPECTIVE ANALYSIS - Memane, Nanasaheb; Shanke, A (International Journal of Ayurveda and Pharma Research, 2015)
Bronchial asthma is a widely occurring respiratory tract disorder with a poor quality of life, associated with adverse reactions and many achieve incomplete cure. Recently, an integrated approach of allopathy with lifestyle management, psychosocial approaches and evidence based complementary medicine has been promoted in the management of bronchial asthma. Hence, the present study was undertaken to evaluate the same. Methods: The present study was a retrospective analysis of patients diagnosed as asthmatics who were being managed through integrated approach that includes a combination of ayurvedic drugs, lifestyle management and the allopathic agents. The ayurvedic drugs include the respiratory tonics and naturally occurring bronchodilators such as Shwaskaschintamani, Shwaskuthar ras, Vasakasavam, Vasavleham, Mahalaxmivilas rasa. The allopathic drugs include short and long-acting beta-2 agonists and inhalational corticosteroids depending on the intensity of bronchial asthma. Results: A total of 36 children and 71 adults were identified as asthmatics with a median (range) age (in years) of 8 (2-13) and 46 (18-64). A significant resolution of all the symptoms except for hyperacidity was observed at all the follow-up periods as compared to the baseline (P < 0.05). Conclusion: A holistic approach of adding alternative therapies to the conventional pharmacotherapy offers the asthmatic patients a potential to safely control their symptoms in Indian patients.